2006
DOI: 10.7150/ijms.3.108
|View full text |Cite
|
Sign up to set email alerts
|

Association of the T+294C polymorphism in PPAR δ with low HDL cholesterol and coronary heart disease risk in women

Abstract: Background: The +T294C polymorphism in PPARδ represents a functional SNP affecting transcriptional activity of the PPARδ gene. To address whether this polymorphism is associated with the risk for coronary heart disease and/or plasma lipid levels in women, we studied a group of 967 female patients with hyperlipidaemia in the presence (n=453) or absence (n=514) of coronary heart disease.Methods: 967 female patients with or without coronary heart disease were genotyped using mutagenically separated polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 12 publications
1
35
0
5
Order By: Relevance
“…The minor allele of the rs2016520 variant in exon 4 has inconsistently been associated with decreased fasting levels of HDL-cholesterol [15], increased LDL-cholesterol a Regression estimate±SE of the logarithm of HOMA-IR (pmol/l×mmol/l) with haplotype 1 (A-C) as base Haplotype frequencies were estimated using the EM algorithm and association with quantitative traits was evaluated by global and haplotypespecific score statistics ( p value) and simulation (p SIM ) [31] Estimates of the effect sizes of each haplotype were estimated by modelling the haplotype×phenotype interaction [32] [16,17] and increased fasting plasma glucose [37] or decreased BMI [20], even though some studies found no association [19,21]. Yet all studies were probably statistically underpowered, involving fewer than 1,000 participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minor allele of the rs2016520 variant in exon 4 has inconsistently been associated with decreased fasting levels of HDL-cholesterol [15], increased LDL-cholesterol a Regression estimate±SE of the logarithm of HOMA-IR (pmol/l×mmol/l) with haplotype 1 (A-C) as base Haplotype frequencies were estimated using the EM algorithm and association with quantitative traits was evaluated by global and haplotypespecific score statistics ( p value) and simulation (p SIM ) [31] Estimates of the effect sizes of each haplotype were estimated by modelling the haplotype×phenotype interaction [32] [16,17] and increased fasting plasma glucose [37] or decreased BMI [20], even though some studies found no association [19,21]. Yet all studies were probably statistically underpowered, involving fewer than 1,000 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the variation in PPARD in relation to features of the metabolic syndrome have resulted in conflicting results. Several studies including fewer than 1,000 participants have investigated the c. −87T→C (rs2016520) variant in exon 4 in relation to serum lipid profiles and have shown a positive association of the minor C allele with higher serum levels of LDL-cholesterol [15], lower HDL-cholesterol [16,17], higher triacylglycerol [18] or no association [19][20][21]. In addition, a recent paper reported that three variants in PPARD and a haplogenotype of these variants were associated with increased insulinstimulated whole-body and skeletal muscle glucose uptake in a study including 129 carefully phenotyped subjects [22].…”
Section: Introductionmentioning
confidence: 99%
“…KKH olan ve olmayan kadın hiperlipidemik bireylerde incelenmesi sonucu polimorfizmin KKH ve plazma lipid düzeyleri ile ilişkili olduğu gözlen-miştir. 13 Bu çalışmanın bulgularına göre göre, PPAR-B/D +294T/C polimorfizmi yüksek VLDL ve LDL düzeyleriyle ilişkilidir. Bununla birlikte, minör C allelinin düşük plazma HDL düzeyleri üzerinden KKH ve BKİ ile ilişkili olduğu da göste-rilmiştir.…”
Section: Discussionunclassified
“…10 PPAR'ların dokulardaki dağılımı farklı olup tüm vücuttaki lipid ve glukoz metabolizması üzerinde birbirinden farklı, ancak zaman zaman örtüşen görevler üstlenen alfa, beta/delta ve gama olarak adlandırılmış üç izoformu bulunmaktadır. 10,12,13 PPAR ailesi, uzun zincirli yağ asitlerinden ökozonoidlere çeşitli endojen ligandlarla aktive edilebilmektedir. Bu özellikleri nedeniyle dislipidemi, diyabet, obezite, adiposit farklılaşması, inflamasyon ve kanser gibi çok sayıda hastalığın tedavisine yönelik terapötik amaçlı sentetik PPAR ligandları üretilmiştir.…”
unclassified
See 1 more Smart Citation